Psychiatric symptoms and disorders associated with reproductive cyclicity in women: advances in screening tools. (June 2015) - Hall, Elise; Steiner, Meir
Female-specific psychiatric illness including premenstrual dysphoria, perinatal depression, and psychopathology related to the perimenopausal period are often underdiagnosed and treated. These conditions can negatively affect the quality of life for women and their families. The development of screening tools has helped guide our understanding of these conditions. There is a wide disparity in the methods, definitions, and tools used in studies relevant to female-specific psychiatric illness. As a result, there is no consensus on one tool that is most appropriate for use in a research or clinical setting. In reviewing this topic, we hope to highlight the evolution of various tools as they have built on preexisting instruments and to identify the psychometric properties and clinical applicability of available tools. It would be valuable for researchers to reach a consensus on a core set of screening instruments specific to female psychopathology to gain consistency within and between clinical settings.